1981
DOI: 10.1161/01.cir.64.3.477
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and cardiac function.

Abstract: SUMMARY We studied 10 obese volunteers, mean age 36.5 ± 10.3 years, who weighed 123.56 ± 28.7 kg and were 69.96 ± 22.5 kg overweight. The subjects did not have diabetes, arterial hypertension or signs of cardiac and respiratory failure or disease and all underwent right-and left-heart catheterization. Cardiac output and stroke volume were high, according to increased oxygen consumption and to the degree of obesity. Ventricular end-diastolic and atrial pressures ranged from normal to high and correlated with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
129
3
24

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(174 citation statements)
references
References 31 publications
15
129
3
24
Order By: Relevance
“…Previous population studies have demonstrated that RVSP increases with age (8)(9)(10)(11), BMI (8,12) and sex (8). Unlike other studies, ours did not find sex, BMI or any LV dimension to be significant using multivariate analysis, although most were significant using bivariate analysis.…”
Section: Discussioncontrasting
confidence: 92%
“…Previous population studies have demonstrated that RVSP increases with age (8)(9)(10)(11), BMI (8,12) and sex (8). Unlike other studies, ours did not find sex, BMI or any LV dimension to be significant using multivariate analysis, although most were significant using bivariate analysis.…”
Section: Discussioncontrasting
confidence: 92%
“…The meaningful alterations observed in the LV isovolumic relaxation time are worth emphasizing, in addition to the relative enhancement of the atrial contraction A wave, which reflects a clear incipient difficulty imposed on ventricular filling in the healthy obese. The signs of diastolic dysfunction preceding systolic impairment were also observed in the Di Devitiis et al 13 study. Concomitantly, all indexes of either global or segment systolic function were within normal limits, making believe one that the alterations found are part of a context, or better yet, of a clinical and hemodynamic situation still in a compensated state.…”
Section: Referencessupporting
confidence: 68%
“…Obesity is independently associated with increased LV mass (Figure 3), an adverse prognostic factor in HCM, contributing to more rapid clinical progression and worsening of heart failure symptoms 64. Interestingly, however, LV mass increase in obese patients with HCM seems to merely reflect LV cavity enlargement, physiologically aimed at increasing cardiac output65 to meet the increased requirements of excessive body weight. Conversely, maximal LV thickness is similar in normal weight versus obese patients with HCM, suggesting that the genetic design of asymmetric septal LVH is independent of body mass index 48.…”
Section: Acquired Comorbiditiesmentioning
confidence: 99%